Kant - Scruton, Roger (Oxford Oxford university press, 1982)
Kant is arguably the most influential modern philosopher, but also one of the most difficult. Roger Scruton tackles his exceptionally complex subject with a strong hand, exploring the background to Kant's work and showing why the Critique of Pure Reason has proved so enduring. ABOUT THE SERIES: The Very Short Introductions series from Oxford University Press contains hundreds of titles in almost every subject area. These pocket-sized books are the perfect way to get ahead in a new subject quickly. Our expert authors combine facts, analysis, perspective, new ideas, and enthusiasm to make interesting and challenging topics highly readable.